2022
DOI: 10.3390/healthcare10101954
|View full text |Cite
|
Sign up to set email alerts
|

The Increased Mortality Rate with Lower Incidence of Traumatic Brain Injury during the COVID-19 Pandemic: A National Study

Abstract: Background: the COVID-19pandemic with the following lockdown strategies have affected virtually all aspects of everyday life. Health services all over the world faced the crisis on an unprecedented scale, hampering timely care delivery. The present study was designed to assess the impact of the COVID-19 outbreak on the incidence and treatment of traumatic brain injuries in Poland. Methods: the data on hospital admissions with traumatic brain injuries as the primary diagnosis were extracted from the National He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…However, there were no obvious differences in the apoptosis of neurons between the 1 and 2 μg/ml groups. Thus, we examined the ultrastructure and expression of ERS markers including p-PERK, GRP78, ATF4 and CHOP in neuron-2a cells after they were treated with 0, 0.5 or 1 μg/ml eCIRP for 48 h. The results confirmed that eCIRP treatment, especially at a dose of 1 μg/ml, could activate apoptosis pathways related to ERS in neuron-2a cells and upregulate the expression of p-PERK, GRP78, ATF4 and CHOP in neuron-2a cells (interaction F [ 6 , 24 ] = 0.41, p = 0.861; group F [ 2 , 24 ] = 51.35; p < 0.001, Figure 3b ) and cause significant expansion of the ER ( Figure 3c ).…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…However, there were no obvious differences in the apoptosis of neurons between the 1 and 2 μg/ml groups. Thus, we examined the ultrastructure and expression of ERS markers including p-PERK, GRP78, ATF4 and CHOP in neuron-2a cells after they were treated with 0, 0.5 or 1 μg/ml eCIRP for 48 h. The results confirmed that eCIRP treatment, especially at a dose of 1 μg/ml, could activate apoptosis pathways related to ERS in neuron-2a cells and upregulate the expression of p-PERK, GRP78, ATF4 and CHOP in neuron-2a cells (interaction F [ 6 , 24 ] = 0.41, p = 0.861; group F [ 2 , 24 ] = 51.35; p < 0.001, Figure 3b ) and cause significant expansion of the ER ( Figure 3c ).…”
Section: Resultsmentioning
confidence: 56%
“…BV2 cells were transfected with CIRP-siRNA or NC, and 24 h later they were treated with 1 μg/ml LPS for 24 h. The expression of H3K9ac in different cells was examined via WB analysis, and the untreated BV2 cells that were transfected with NC served as the control. The results showed that CIRP knockdown in BV2 cells alleviated the decreases in H3K9ac and α7nAChR expression, thus attenuating the increase in L-1β and TNF-α expression induced by LPS stimulation (interaction F [ 8 , 30 ] = 21.32, p < 0.001; group effect F [ 2 , 30 ] = 3.335, p < 0.05; Figure 8b ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Colcuc et al included only severely injured patients, while in this paper, we analyzed the entire trauma population of Lublin Province. Miekisiak et al, in the national analysis of TBI incidence in Poland, found that the volume of TBI in 2020 dropped by almost 25% in comparison with the previous six years, with a significant reduction in conservatively treated patients [54]. In several single-center analyses of TBI epidemiology during the lockdown period, a decrease in head trauma was reported during the time of COVID-19 restrictions [55][56][57][58][59].…”
Section: Anatomic Description Of Injurymentioning
confidence: 99%